2015
DOI: 10.1007/s00268-015-3205-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Muscle Attenuation in Pancreatic Cancer Patients Treated with Neoadjuvant Chemoradiotherapy

Abstract: Muscle attenuation may have a significant impact in pancreatic cancer patients treated with multimodal therapy. Therefore, our data may provide new insights into perioperative patient care to improve the prognosis of resectable pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 61 publications
3
70
0
Order By: Relevance
“…For articles that remained after the initial screen, 65 full texts were reviewed for eligibility. Ultimately, 24 studies were selected for inclusion in the systematic review-18 articles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]47] and 6 abstracts [33, 44-46, 48, 53]-with a total of 3,607 patients. Table 2 provides an overview of included studies regarding number of study participants, cancer types, inclusion criteria, and stage of care when the BIA assessment was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…For articles that remained after the initial screen, 65 full texts were reviewed for eligibility. Ultimately, 24 studies were selected for inclusion in the systematic review-18 articles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]47] and 6 abstracts [33, 44-46, 48, 53]-with a total of 3,607 patients. Table 2 provides an overview of included studies regarding number of study participants, cancer types, inclusion criteria, and stage of care when the BIA assessment was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…This is important as preoperative sarcopenia has been shown to be an important risk factor for postoperative complications following pancreatectomy [21–28] and that some studies have demonstrated either a decrease in SKM [8] or muscle attenuation [11] during preoperative therapy for PDAC. In fact, we previously showed that minor changes in SKM, VAT and SAT occur during preoperative therapy for PDAC but that these changes did not preclude subsequent pancreatectomy nor were they associated with survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that clinically significant anthropometric changes occur during neoadjuvant therapy for various malignancies [911]. However, the anthropometric and nutritional changes that occur following curative therapy for localized PDAC and throughout the survivorship period have not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that measure body composition with CT analysis attempt to identify the prognostic ability of skeletal muscle cross‐sectional area, or changes in skeletal muscle attenuation values (ie, HUs) at a single time point 10 , 12 – 21 , 32 35 . In general, skeletal muscle cross‐sectional area and muscle attenuation are often demonstrated to have strong prognostic values—with lower cross‐sectional area or reduced attenuation values being associated with worse outcomes.…”
Section: Ctmentioning
confidence: 99%
“…Some investigators have attempted to use average CT HUs as a way to evaluate muscle quality , but the validity of this practice is not clear 10 , 11 , 33 , 34 , 37 . This will need to be validated through studies that include muscle biopsies.…”
Section: Ctmentioning
confidence: 99%